Strategies for Developing Family Nursing Communities of Practice Through Social Media. (February 2017) - Isaacson, Kris; Looman, Wendy S.
This discussion article presents communities of practice (CoPs) and bridging social capital as conceptual frameworks to demonstrate how social media can be leveraged for family nursing knowledge, scholarship, and practice. CoPs require a shared domain of interest, exchange of resources, and dedication to expanding group knowledge. Used strategically and with a professional presence, mainstream social media channels such as Twitter, Facebook, and YouTube can support the family nurse in developing and contributing to CoPs related to family nursing. This article presents four strategies—curate, connect, collaborate, and contribute—for establishing and growing a social media presence that fits one's professional goals and time availability. Family nurses who leverage social media using these strategies can strengthen existing CoPs and at the same time bridge networks to reach new audiences, such as family advocacy groups, policy makers, educators, practitioners, and a wide array of other extended networks.